Impulsivity and sensitivity to reward as mediating factors of the negative relationship between emotional intelligence and health-related risk-taking: evidence from a sample of university students - Alberto Megías-Robles; María T. Sánchez-López; Raquel Gómez-Leal; Rosario Cabello; María José Gutiérrez-Cobo; Pablo Fernández-Berrocal (BMC Psychology, 2023)
Abstract Background Better abilities in emotional intelligence (EI) have been linked to a decreased tendency to engage in health-related risk behaviour. However, the processes underlying this relationship are still unclear. The aim of this research was to examine the role of impulsivity and sensitivity to reward as mediating factors in the relationship between EI and health risk-taking. Methods Two hundred and fifty participants (Mage = 23.60, age range = 18–59; SD = 6.67; 71.60% women) were assessed on ability EI levels, risk-taking in health contexts, impulsivity, and sensitivity to reward. Unlike previous studies in the literature, we employed a performance-based ability measure to assess EI (Mayer-Salovey-Caruso Emotional Intelligence Test, MSCEIT). Results The results confirmed the negative relationship between EI and health risk-taking and revealed the existence of a significant negative indirect effect of EI on health-risk taking through various dimensions of impulsivity and sensitivity to reward. EI abilities —particularly the ability to manage emotions— were associated with lower levels of impulsivity under positive and negative emotional states, a better management of the tendency towards sensation seeking, and a decreased emotional reactivity to rewards. Conclusions The present research provides a better understanding of the processes underlying the negative relationship between EI and health risk-taking. Our findings suggest that having higher levels of EI abilities would allow for a more objective evaluation of risk scenarios and a more appropriate and safer decision making through its influence on the levels of impulsivity and emotional reactivity to rewards. Practical implications, limitations, and future lines of research are discussed.